2020
DOI: 10.18273/revbol.v42n2-2020002
|View full text |Cite
|
Sign up to set email alerts
|

Shallow intraplate seismicity in the Buenos Aires province (Argentina) and surrounding areas: is it related to the Quilmes Trough?

Abstract: In the light of the November 30th, 2018 (N30) earthquake activity, some neighborhoods of the city of Buenos Aires were shaken by a 3.8 mb earthquake (4.53 km estimated depth). We examined the historical and recent seismic records in order to analyze possible mechanisms related to the distribution of tectonic stresses as responsible for such unusual earthquakes in a region where only very little seismic activity is reported. According to this, at list one historical event occurred on June 5t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…From the tectonic point of view, the Pacific margin of South America is subjected to compression since the Mesozoic when the Nazca-South America convergence established a sub-latitudinal deformation regime (Brooks et al, 2003;Sperner et al, 2003;Cobbold et al, 2005;Costa et al, 2006;Guzmán et al, 2007). The revised and updated compilation of focal mechanisms in intraplate South America shows that horizontal compressional stresses predominate, not only in the Andean foreland belt, but also in mid-plate areas of the continent (Assumpção et al, 2016;Rossello et al, 2020). The cited works allow assuming the current maximum horizontal stress orientation for the Pampean region with an azimuth of 80º, which is slightly oblique with respect to the EVC, putting in evidence the right-lateral component of the wrench faulting (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the tectonic point of view, the Pacific margin of South America is subjected to compression since the Mesozoic when the Nazca-South America convergence established a sub-latitudinal deformation regime (Brooks et al, 2003;Sperner et al, 2003;Cobbold et al, 2005;Costa et al, 2006;Guzmán et al, 2007). The revised and updated compilation of focal mechanisms in intraplate South America shows that horizontal compressional stresses predominate, not only in the Andean foreland belt, but also in mid-plate areas of the continent (Assumpção et al, 2016;Rossello et al, 2020). The cited works allow assuming the current maximum horizontal stress orientation for the Pampean region with an azimuth of 80º, which is slightly oblique with respect to the EVC, putting in evidence the right-lateral component of the wrench faulting (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The right lateral EVC involves basement levels and suggests the flow of crustal material farther east, possibly facilitating the widening of Cenozoic depocenters located in the Atlantic margin such as those documented by Rossello et al (2017). Richardson et al (2013) argued that the increased coupling between the subducting flat slab and the overriding plate beneath the Andean Cordillera at 32ºS resulted in the propagation of Neogene and Quaternary crustal deformation eastward to the Rio de la Plata craton (Rossello et al, 2020). In this sense, the EVC located far East could constitute the prolongation of a major slab discontinuity zone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rossello et al (2011) identified first-order structural features with subparallel highs and lows and matching general ENE-WSW directions in the basement, similar to those in the Santa Lucía basin, and with extensional tectonics related to the Gondwana breakup and the early opening of the Atlantic Ocean (Figure 3). This structuring is considered to be one of the factors responsible for the 3.8-degree earthquake recorded approximately 20 km south of Buenos Aires on November 30, 2018, with an estimated epicenter of approximately 4.5 km (Rossello et al, 2020).…”
Section: Quilmes Tectonic Troughmentioning
confidence: 99%